Effects of scrotal insulation in Nellore bulls (Bos taurus indicus) on seminal quality and its relationship with in vitro fertilizing ability - Fernandes, C. E.; Dode, M. A.N.; Pereira, D.; Silva, A. E.D.F. [UNESP] (Elsevier, 2008)
The objectives of this study were to assess the effects of induced testicular degeneration in Bos taurus indicus (Nellore) bulls on changes in seminal characteristics and fertilizing ability of sperm. Four Nellore bulls (30-36-month-old, 500-550 kg) with good seminal quality (>80% motile and morphologically normal sperm) had scrotal insulation applied for 5 d. Semen was collected by electroejaculation and cryopreserved at the pre-insulation moment, and 7, 14, and 21 d after insulation was removed. Gross motility, vigor of sperm movement (1-5), acrosome integrity, sperm morphology (phase-contrast microscopy), nuclear vacuoles and abnormal chromatin (Feulgen-stain) were determined after sperm preparations for in vitro fertilization (IVF). Prior to IVF, sperm were separated using a Percoll gradient (45% and 90%). Normal sperm decreased (P < 0.05) 14 and 21 d after insulation was removed. On 14 and 21 d, the incidence of head defects (9.7 ± 0.6 and 17.0 ± 0.8, respectively; mean ± S.E.M.) was higher (P < 0.05) in agreement with the incidence of nuclear vacuoles (14.0 ± 5.0 and 12.3 ± 2.3) and abnormal chromatin (24.4 ± 7.2 and 30.8 ± 2.8). Although the frequency of cleaved oocytes decreased only on 21 d (P < 0.05), blastocyst rates were lower (P < 0.05) than pre-insulation on 14 and 21 d. In regression analyses, only nuclear vacuoles, head defects and intact acrosome accounted for differences in cleavage (R2 = 0.38, 0.48, and 0.30, respectively) and blastocyst rates (R2 = 0.35, 0.37, and 0.44). Abnormal chromatin was associated only with blastocyst rates (R2 = 0.35). In conclusion, blastocyst rate was more sensitive than cleavage rate and the assessment of nuclear integrity is recommended to predict the fertilizing ability of bull sperm. © 2008 Elsevier Inc. All rights reserved.
Keywords: Abnormal sperm chromatin; Bovine semen; Fertilization; Sperm morphology